2012
DOI: 10.1016/j.jacc.2012.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition and Survival in Stable Coronary Heart Disease

Abstract: In patients with stable CHD, both LMI and BF predict mortality, with mortality particularly high in those with Low LMI/Low BF and lowest in those with High LMI/High BF. Determination of optimal body composition in primary and secondary CHD prevention is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(75 citation statements)
references
References 26 publications
3
63
1
8
Order By: Relevance
“…Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Likewise, sarcopenia, defined as a loss of muscle mass and associated with frailty and overall decreased functionality and increased mortality, could have harmful effects in patients with CAD, as our results suggest 23, 24, 25…”
Section: Discussionmentioning
confidence: 60%
“…There are only a few studies assessing the relationship of BF content and mortality in patients with CAD, and they have used the skin fold method to assess body fatness 23, 27. This technique has proved to be not better than BMI to assess body composition,39 and this probably explains why those studies still show a paradoxical association between low fat and increased mortality, similar to studies using BMI as a measure of fatness 3…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential adverse effects of overweight and obesity on CVD risk factors and incidence, numerous investigators and meta-analysis of studies in cohorts with CHD have shown increased survival in those who are overweight or obese (6)(7)(8)(9)(10) when defined by high BMI, the obesity paradox, although this has not been seen in all studies after adjustment for confounders (64,65) . In the RICO Survey, a study of over 2000 patients with acute myocardial infarction, an inverse association was seen between BMI and mortality but this was attenuated after adjustment for factors associated with survival, including prior myocardial infarction, hypertension, diabetes, hyperlipidaemia, smoking and left ventricular ejection fraction (64) .…”
Section: The Obesity Paradox In Those With Chdmentioning
confidence: 99%
“…However, there is controversy surrounding the effects of overweight and obesity in older people, with many studies showing that being overweight, as defined by BMI of 25-29 kg/m 2 , does not appear to be as harmful in the elderly as in middle-aged populations and may even be associated with lower, rather than higher, mortality (3)(4)(5) . In addition, a large body of evidence indicates that overweight and obesity (BMI ⩾ 25 kg/m 2 ) are associated with increased survival in patients with CVD and in particular those with heart failure, an unexpected finding termed the obesity paradox (6)(7)(8)(9)(10) . The mechanisms of these paradoxical association remain largely unexplained but a number of explanations have been proposed (11,12) .…”
mentioning
confidence: 99%
“…[39] 2.4.2 Heart, renal, and respiratory diseases Sarcopenia is also associated with adverse outcomes in patients diagnosed with cardiovascular disease and heart failure. [40][41][42] In a study examining body composition and 3-year mortality in patients with heart disease, individuals with stable heart disease and low lean body mass had a 15% increase in mortality compared to those individuals with a higher lean body mass. [41] Similar findings have been reported in patients diagnosed with renal failure.…”
Section: Cancermentioning
confidence: 99%